Design and development of a model and optimal planning for supply chain responsibility towards the environment (Nexo Revista Científica, 2021)
The responsible management of product return flows in production and inventory environments is a rapidly increasing requirement for companies. This can be attributed to economic, environmental and/or regulatory motivations. Mathematical modeling of such systems has assisted decision-making processes and provided a better understanding of the behavior of such production and inventory environments. This paper reviews the literature on the modeling of reverse logistics inventory systems based on the economic order/production quantity (EOQ/EPQ) and the joint economic lot size (JELS) settings to systematically analyze the mathematics involved in capturing the main characteristics of related processes. The literature is surveyed and classified according to the specific issues faced and modeling assumptions. Special attention is given to environmental issues. There are indications of the need for reverse logistics models' mathematics to follow current trends in ‘greening’ inventory and supply-chain models. The modeling of waste disposal, greenhouse-gas emissions, and energy consumption during production is considered as the most pressing priority for the future of reverse logistics models. An illustrative example for modeling reverse logistics inventory models with environmental implications is presented.